Three Notes on the Economic Performance of Migrants - Oded Stark; Eliakim Katz; Oded Galor (Harvard University, Center for Population Studies Cambridge, 1988)
D.P. 37. Migrants and Markets: In recent research, the question "Why do migrants fare as they do?" has largely been answered through an inspection of the vector of migrants' characteristics. The main theme of the current paper is that special features characterize the interaction (the nature of trades) between migrants and the markets they join and that market characteristics largely account for the labour market performance of individual migrants. D.P. 38. Why Do Migrants Fare as They Do?: This paper offers a new explanation for the often observed higher mean income - higher income variance of migrants vis-à-vis the native-born, The explanation is based on the relative lack of information about migrants in the receiving country rather than on the attributes of migrants, It accounts for several important stylized facts and generates predictions different from those of the attributes explanation. D.P. 39. Migrants' Savings, the Probability if Return Migration and Migrants' Performance: This paper highlights a difference between migrants and the native-born viz., a positive probability of return migration. An overlapping-generations model is used to show that this probability results in migrants' saving more than comparable native-born. This differential helps explain why migrants often outperform the native-born in the receiving economy.
Keywords: 330